Visualizing fractional control system approximations by means of multidimensional scaling - Tenreiro Machado, J. A. (2011)
This paper addresses the use of multidimensional scaling in the evaluation of fractional system approximations. Algorithms are analysed based on the time response of the closed loop system under the action of a reference step input signal. Two alternative performance indices, based on the time and frequency domains, are tested. The numerical experiments demonstrate the feasibility of the proposed methodology.